Public Participation in the Operations of Kalupang Subdistrict Administrative Organization, Raman District, Yala Province - สาเล็งบาเกาะ อารีนา; สุหลง ตัสนีม; มูเน๊าะ อีรฟาน; มินทราศักดิ์ นินุสรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) study the level of public participation in the operations of the Kalupang Subdistrict Administrative Organization, Raman District, Yala Province; and 2) propose guidelines for developing public participation in the operations of the Kalupang Subdistrict Administrative Organization, Raman District, Yala Province. This study employed a quantitative research method. The population consisted of 2,341 residents living within the jurisdiction of the Kalupang Subdistrict Administrative Organization. The sample size was determined using Yamane’s formula, resulting in 342 respondents. The sampling technique used was proportionate stratified sampling according to each village, followed by simple random sampling. A questionnaire was used as the research instrument, and the data were analyzed using descriptive statistics. The research findings revealed that the overall level of public participation was at a high level (x̄= 3.47). When considering each aspect, participation in receiving benefits had the highest mean score (x̄= 3.62), followed by participation in implementation (x̄= 3.46) and participation in decision-making (x̄= 3.45). Participation in evaluation had the lowest mean score (x̄= 3.33), which was at a moderate level. This indicates that the public generally recognizes the benefits and cooperates well in the implementation of local government operations. However, participation in monitoring, evaluation, and providing feedback should be further promoted to enhance transparency and support sustainable development in the future.